Stiind că x-2×y+13=52,determinați 3×x-6×y+1
Răspunsuri la întrebare
Răspuns de
1
x - 2 y + 13 = 52
x - 2 y = 52 - 13
x - 2 y = 39
3 x - 6 y + 1 = 118
= 3 ( x - 2 y) + 1 =
= 3 × 39 + 1 =
= 117 + 1 =
= 118
x - 2 y = 52 - 13
x - 2 y = 39
3 x - 6 y + 1 = 118
= 3 ( x - 2 y) + 1 =
= 3 × 39 + 1 =
= 117 + 1 =
= 118
Alte întrebări interesante
Engleza,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Informatică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă